Kyrgyz Republic : First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report, 2005)
This paper discusses the Kyrgyz Republic's First Review Under the Poverty Reduction and Growth Facility. The current account deficit remained broadly unchanged because of a significant increase in workers' remittances, mainly from Russia and Kazakhstan. Large negative errors and omissions in the balance of payments suggest that the spring political events led to some capital flight. Structural reforms will continue to focus on developing the financial sector, addressing energy sector imbalances, and increasing labor market flexibility.